A Review of the Foraminiferal Biostratigraphy of the Melinau Limestone, Sarawak - Peter Lunt (Berita Sedimentologi, 2014)
A study of the Melinau limestone, especially in the continuous Melinau Gorge section, reviews taxonomic concepts of Adams (1965) in the Heterostegina- Tansinhokella- Spiroclypeus lineage, proves the presence of Middle Eocene 'Letter Stage' Ta, at the base of the Melinau Limestone, examines the nature of the Eocene- Oligocene boundary and the absence of Wilfordia sarawakensis Adams from other Tb Eocene limestones in the region. Strontium dating and biostratigraphy calibrated to GTS04 shows there to be a significant change in sedimentary rates or preserved thickness during mid-Oligocene (latest Tc or intra-Td times), but the disconformity noted by Adams (1970) was not found, probably due to poor exposure. Observations on the termination of the Melinau limestone agree with those of Adams (1965, 1970) and Wannier (2009), with an initial event near the Oligo-Miocene boundary (Te4 to Te5 boundary) and the youngest limestones dated as Te5, about 20.3 Ma.